Psychological Benefits and Challenges of Ph.D. Entrance Exam Virtual Interviews During COVID-19 Pandemic: Does Gender Play a Role? - Ebadi, Saman; Bashiri, Saba (Frontiers in Psychology, 2021)
This study aimed to investigate the reflections of Iranian students on Ph.D. entrance exam interviews held virtually nationwide during the Pandemic. Two hundred thirty-one Ph.D. applicants were invited to fill out an anonymous online survey designed in Google Forms, 36 out of whom volunteered to participate in follow-up semi-structured interviews. Two ANOVA measures were used to investigate the possible influences of gender and prior virtual interview experience on the applicants’ perceptions. Thematic analysis was also adopted to explore the participants’ attitudes and perceptions toward virtual interviews. Quantitative findings showed that Iranian Ph.D. applicants perceived virtual interviews as a flexible and helpful procedure that provided them with satisfactory interpersonal treatment. Still, they did not favor the procedure’s perceived behavioral control and ability to communicate information to perform procedural justice. Moreover, neither their gender nor their prior experience of the virtual interview was a predictor of their perspectives' discrepancies. The thematic analysis of the qualitative data revealed that despite having some cognitive, personal, and financial benefits, virtual interviews posed some technical, communicative, and personal challenges. This study provides implications for universities and applicants who will use virtual interviews for different purposes in higher education.